Automated production of specific T cells for treatment of refractory viral infections after allogeneic stem cell transplantation - Heinz, Amadeus T.; Calkoen, Friso G.J.; Derbich, Alexander; Miltner, Lea; Seitz, Christian; Doering, Michaela; Braun, Christiane; Atar, Daniel; Schumm, Michael; Heubach, Florian; Arendt, Anne Marie; Schulz, Ansgar; et al. (Haematologica, 2023)
Therapy-resistant viral reactivations contribute significantly to mortality after hematopoietic stem cell transplantation. Adoptive cellular therapy with virus-specific T cells (VST) has shown efficacy in various single-center trials. However, the scalability of this therapy is hampered by laborious production methods. In this study we describe the in-house production of VST in a closed system (CliniMACS Prodigy® system, Miltenyi Biotec). In addition, we report the efficacy in 26 patients with viral disease following hematopoietic stem cell transplantation in a retrospective analysis (adenovirus, n=7; cytomegalovirus, n=8; Epstein-Barr virus, n=4; multi-viral, n=7). The production of VST was successful in 100% of cases. The safety profile of VST therapy was favorable (n=2 grade 3 and n=1 grade 4 adverse events; all three were reversible). A response was seen in 20 of 26 patients (77%). Responding patients had a significantly better overall survival than patients who did not respond (P<0.001). Virus-specific symptoms were reduced or resolved in 47% of patients. The overall survival of the whole cohort was 28% after 6 months. This study shows the feasibility of automated VST production and safety of application. The scalability of the CliniMACS Prodigy® device increases the accessibility of VST treatment.
CRIS-Team Scopus Importer:2023-08-11

High-dose chemotherapy (HDCT) with auto-SCT in children with atypical teratoid/rhabdoid tumors (AT/RT): a report from the European Rhabdoid Registry (EU-RHAB) - Benesch, M.; Bartelheim, K.; Fleischhack, G.; Gruhn, B.; Schlegel, P. G.; Witt, O.; Stachel, Daniel; Hauch, H.; Urban, C.; Quehenberger, F.; Massimino, M.; Pietsch, T.; et al. (Bone Marrow Transplantation, 2014)
A retrospective analysis of data from the European Rhabdoid Registry (EU-RHAB) was performed to describe the outcome of children with atypical teratoid/rhabdoid tumors (AT/RT) who underwent high-dose chemotherapy (HDCT) with auto-SCT. Nineteen patients (male, n=15; median age at diagnosis 21 months) were identified. Nine patients presented with metastatic disease at diagnosis. A partial or subtotal resection was achieved in 11, a total resection in five and a biopsy in three patients. Patients received a median of six chemotherapy cycles prior to HDCT. Additional radiotherapy was performed in 14 patients (first-line, n=9; following progression, n=5). Six patients underwent tandem auto-SCT. Disease status before HDCT was CR in six, PR in eight, stable disease in two and progressive disease (PD) in two patients (data missing, n=1). With a median follow-up of 16 months, 14 patients progressed. Estimated progression-free and OS at 2 years were 29% (±11%) and 50% (±12%), respectively. At last follow-up, eight patients were alive (first CR, n=4; second CR, n=2; PR, n=1; PD, n=1). Eleven patients died of PD. Median time-to-progression was 14 months. Selected patients with AT/RT might benefit from HDCT with radiotherapy. The definitive impact of this treatment modality has to be evaluated prospectively in a randomized trial.
EVALuna2:18904

Hyperactive mTOR pathway promotes lymphoproliferation and abnormal differentiation in autoimmune lymphoproliferative syndrome - Voelkl, Simon; Rensing-Ehl, Anne; Allgäuer, Andrea; Schreiner, Elisabeth; Lorenz, Myriam Ricarda; Rohr, Jan; Klemann, Christian; Fuchs, Ilka; Schuster, Volker; Von Bueren, Andre O.; Naumann-Bartsch, Nora; Gambineri, Eleonora; et al. (Blood, 2016)
Autoimmune lymphoproliferative syndrome (ALPS) is a human disorder characterized by defective Fas signaling, resulting in chronic benign lymphoproliferation and accumulation of TCR??(+) CD4(-) CD8(-) double-negative T (DNT) cells. Although their phenotype resembles that of terminally differentiated or exhausted T cells, lack of KLRG1, high eomesodermin, and marginal T-bet expression point instead to a long-lived memory state with potent proliferative capacity. Here we show that despite their terminally differentiated phenotype, human ALPS DNT cells exhibit substantial mitotic activity in vivo. Notably, hyperproliferation of ALPS DNT cells is associated with increased basal and activation-induced phosphorylation of serine-threonine kinases Akt and mechanistic target of rapamycin (mTOR). The mTOR inhibitor rapamycin abrogated survival and proliferation of ALPS DNT cells, but not of CD4(+) or CD8(+) T cells in vitro. In vivo, mTOR inhibition reduced proliferation and abnormal differentiation by DNT cells. Importantly, increased mitotic activity and hyperactive mTOR signaling was also observed in recently defined CD4(+) or CD8(+) precursor DNT cells, and mTOR inhibition specifically reduced these cells in vivo, indicating abnormal programming of Fas-deficient T cells before the DNT stage. Thus, our results identify the mTOR pathway as a major regulator of lymphoproliferation and aberrant differentiation in ALPS.
EVALuna2:25746

Incidence of Secondary Malignancies After TBI/VP16 Conditioning for Childhood All - Results of the Prospective ALL-SCT-BFM-2003 Trial - Eichinger, Anna; Glogova, Evgenia; Beier, Rita; Guengoer, Tayfun; Stachel, Daniel; Stachel, Daniel; Lang, Peter; Sauer, Martin; Strahm, Brigitte; Schulz, Ansgar; Gruhn, Bernd; Wawer, Angela; et al. (BONE MARROW TRANSPLANTATION, 2020)
CRIS-Team WoS Importer:2021-01-22

Incidence of subsequent malignancies after total body irradiation-based allogeneic HSCT in children with ALL - long-term follow-up from the prospective ALL-SCT 2003 trial - Eichinger, Anna; Poetschger, Ulrike; Glogova, Evgenia; Bader, Peter; Basu, Oliver; Beier, Rita; Burkhardt, Birgit; Classen, Carl-Friedrich; Claviez, Alexander; Corbacioglu, Selim; Deubzer, Hedwig E.; Greil, Johann; et al. (Leukemia, 2022)
Total body irradiation (TBI)-based conditioning is associated with superior leukemia-free survival in children with ALL undergoing HSCT. However, the risk for subsequent malignant neoplasms (SMN) remains a significant concern. We analyzed 705 pediatric patients enrolled in the prospective ALL-SCT-BFM-2003 trial and its subsequent registry. Patients >2 years received conditioning with TBI 12 Gy/etoposide (n = 558) and children <= 2 years of age or with contraindications for TBI received busulfan/cyclophosphamide/etoposide (n = 110). The 5- and 10-year cumulative incidence of SMN was 0.02 +/- 0.01 and 0.13 +/- 0.03, respectively. In total, 39 SMN (34 solid tumors, 5 MDS/AML) were diagnosed in 33 patients at a median of 5.8 years (1.7-13.4), exclusively in the TBI group. Of 33 affected patients, 21 (64%) are alive at a median follow-up of 5.1 years (0-9.9) after diagnosis of their first SMN. In univariate analysis, neither age at HSCT, donor type, acute GVHD, chronic GVHD, nor CMV constituted a significant risk factor for SMN. The only significant risk factor was TBI versus non-TBI based conditioning. This analysis confirms and quantifies the increased risk of SMN in children with ALL after conditioning with TBI. Future strategies to avoid TBI will need careful tailoring within prospective, controlled studies to prevent unfavorable outcomes.
CRIS-Team WoS Importer:2022-09-23

Malignant epithelioid peripheral nerve sheath tumor with prominent reticular/microcystic pattern in a child: a low-grade neoplasm with 18-years follow-up - Agaimy, Abbas; Stachel, Daniel; Jüngert, Jörg; Radkow, Tanja; Carbon, Roman; Metzler, Markus; Holter, Wolfgang (Applied Immunohistochemistry & Molecular Morphology, 2014)
Malignant peripheral nerve sheath tumors (MPNSTs) constitute <2% of soft tissue neoplasms in children and display a wide histologic spectrum including low-grade and epithelioid variants, although most are high-grade spindle cell sarcomas. Here, we describe an unusual case of a large retroperitoneal epithelioid MPNST diagnosed in a 7-year-old girl without family history or clinical features of neurofibromatosis type 1. The patient was treated by repeated surgical interventions, polychemotherapy, autologous stem cell transplantation, and irradiation therapy. Over the years, she developed multiple disseminated abdominal recurrences but is currently alive with very slowly progressing disseminated intra-abdominal disease 18 years from initial diagnosis. Histologically, the tumor was composed of medium-sized polygonal and ovoid-to-spindled cells set within a copious myxoid matrix with a prominent reticular and microcystic pattern reminiscent of the recently described reticular/microcystic schwannoma. Immunohistochemistry revealed strong and diffuse expression of S100, CD56, CD57, collagen IV, and neuron-specific enolase, with negativity for perineurial cell markers (claudin-1, epithelial membrane antigen, and glucose transporter-1) and other lineage-specific mesenchymal and epithelial antigens. This unusual variant of low-grade MPNST must be differentiated from a variety of other entities, in particular benign perineurioma, myxoid neurofibroma, and benign reticular/microcystic schwannoma. Confinement of the recurrent disease to the abdominal cavity emphasizes the necessity of primary curative wide excision of this highly recurring but nonmetastasizing low-grade neoplasm.
EVALuna2:6527

Monitoring of minimal residual disease after allogeneic stem-cell transplantation in relapsed childhood acute lymphoblastic leukemia allows for the identification of impending relapse: results of the ALL-BFM-SCT 2003 trial - Bader, Peter; Kreyenberg, Hermann; Von Stackelberg, Arend; Eckert, Cornelia; Salzmann-Manrique, Emilia; Meisel, Roland; Poetschger, Ulrike; Stachel, Daniel; Schrappe, Martin; Alten, Julia; Schrauder, Andre; Schulz, Ansgar; et al. (Journal of Clinical Oncology, 2015)
To elucidate the impact of minimal residual disease (MRD) after allogeneic transplantation, the Acute Lymphoblastic Leukemia Berlin-Frankfurt-Münster Stem Cell Transplantation Group (ALL-BFM-SCT) conducted a prospective clinical trial.In the ALL-BFM-SCT 2003 trial, MRD was assessed in the bone marrow at days +30, +60, +90, +180, and +365 after transplantation in 113 patients with relapsed disease. Standardized quantification of MRD was performed according to the guidelines of the Euro-MRD Group.All patients showed a 3-year probability of event-free survival (pEFS) of 55%. The cumulative incidence rates of relapse and treatment-related mortality were 32% and 12%, respectively. The pEFS was 60% for patients who received their transplantations in second complete remission, 50% for patients in >= third complete remission, and 0% for patients not in remission (P = .015). At all time points, the level of MRD was inversely correlated with event-free survival (EFS; P < .004) and positively correlated with the cumulative incidence of relapse (P < .01). A multivariable Cox model was fitted for each time point, which showed that MRD >= 10(-4) leukemic cells was consistently correlated with inferior EFS (P < .003). The accuracy of MRD measurements in predicting relapse was investigated with time-dependent receiver operating curves at days +30, +60, +90, and +180. From day +60 onward, the discriminatory power of MRD detection to predict the probability of relapse after 1, 3, 6, and 9 months was more than 96%, more than 87%, more than 71%, and more than 61%, respectively.MRD after transplantation was a reliable marker for predicting impending relapses and could thus serve as the basis for pre-emptive therapy.
EVALuna2:18937

NOD2/CARD15 gene polymorphisms affect outcome in pediatric allogeneic stem cell transplantation - Kreyenberg, Hermann; Jarisch, Andrea; Bayer, Christina; Schuster, Blanca; Willasch, Andre; Strahm, Brigitte; Kremens, Bernhard; Gruhn, Bernd; Schrauder, Andre; Burdach, Stefan; Fuehrer, Monika; Rossig, Claudia; et al. (Blood, 2011)
EVALuna2:18787

Presence of centromeric but absence of telomeric group B KIR haplotypes in stem cell donors improve leukaemia control after HSCT for childhood ALL - Babor, Florian; Peters, Christina; Manser, Angela R.; Glogova, Evgenia; Sauer, Martin; Pötschger, Ulrike; Ahlmann, Martina; Cario, Gunnar; Feuchtinger, Tobias; Gruhn, Bernd; Güngör, Tayfun; Horn, Peter A.; et al. (Bone Marrow Transplantation, 2019)
Although allogeneic hematopoietic stem-cell transplantation (HSCT) provides high cure rates for children with high-risk acute lymphoblastic leukaemia (ALL), relapses remain the main cause of treatment failure. Whereas donor killer cell immunoglobulin-like receptor (KIR) genotype was shown to impact on relapse incidence in adult myeloid leukaemia similar studies in paediatric ALL are largely missing. Effect of donor KIR genotype on transplant outcome was evaluated in 317 children receiving a first myeloablative HSCT from an HLA-matched unrelated donor or sibling within the prospective ALL-SCT-BFM-2003 trial. Analysis of donor KIR gene polymorphism revealed that centromeric presence and telomeric absence of KIR B haplotypes was associated with reduced relapse risk. A centromeric/telomeric KIR score (ct-KIR score) integrating these observations correlated with relapse risk (hazard ratio (HR) 0.58; P = 0.002) while it had no impact on graft-versus-host disease or non-relapse mortality. In multivariable analyses ct-KIR score was associated with reduced relapse risk (HR 0.58; P = 0.003) and a trend towards improved event-free survival (HR 0.76; P = 0.059). This effect proved independent of MRD level prior to HSCT. Our data suggest that in children with ALL undergoing HSCT after myeloablative conditioning, donor selection based on KIR genotyping holds promise to improve clinical outcome by decreasing relapse risk and prolonged event-free survival.
CRIS-Team Scopus Importer:2019-05-28

Prospective Clinical Phase II Results on Treosulfan-Based Conditioning Treatment of 70 Paediatric Patients with Haematological Malignancies - Kalwak, Krzysztof; Bader, Peter; Styczynski, Jan; Gruhn, Bernd; Patrick, Katharine; Sedlacek, Petr; Stachel, Daniel; Sykora, Karl-Walter; Corbacioglu, Selim; Drabko, Katarzyna; Fagioli, Franca; Greil, Johann; et al. (BLOOD, 2018)
CRIS-Team WoS Importer:2019-02-27

Systematic comparison of donor chimerism in peripheral blood and bone marrow after hematopoietic stem cell transplantation - Bach, Christian; Steffen, M.; Rösler, Wolf; Winkler, Jürgen; Mackensen, Andreas; Stachel, Daniel; Metzler, Markus; Spriewald, B. M. (Blood Cancer Journal, 2017)
EVALuna2:13436

Treosulfan-based conditioning regimen for children and adolescents with hemophagocytic lymphohistiocytosis - Lehmberg, Kai; Albert, Michael H.; Beier, Rita; Beutel, Karin; Gruhn, Bernd; Kröger, Nicolaus; Meisel, Roland; Schulz, Ansgar; Stachel, Daniel; Woessmann, Wilhelm; Janka, Gritta; Müller, Ingo (Haematologica, 2014)
In hematopoietic stem cell transplantation for hemophagocytic lymphohistiocytosis, high transplant-related mortality after busulfan-based myeloablative regimens has been observed. Conditioning regimens with reduced toxicity based on melphalan or treosulfan are promising alternatives. We retrospectively analyzed hematopoietic stem cell transplantations in 19 hemophagocytic lymphohistiocytosis patients after conditioning with fludarabine, treosulfan, alemtuzumab, with or without thiotepa. Overall and disease-free survivals were 100% (follow up 7-31 months). Two patients required second transplant (1 after haploidentical transplantation). In 6 patients, overall donor chimerism dropped below 75% and prompted donor lymphocyte infusions. Administration of donor lymphocytes or second transplantation were significantly more frequent after transplantation from a human leukocyte antigen mismatched (9/10) versus matched (10/10) donor (P=0.018). The toxicity profile was favorable, with one veno-occlusive disease, one grade 3 graft-versus-host disease after donor lymphocyte infusion, and 2 severe viral infections (1 influenza, 1 Epstein Barr virus). In conclusion, the treosulfan-based regimen in hemophagocytic lymphohistiocytosis is effective with low toxicity and gives excellent overall and disease-free survival rates. In the future, the incidence of mixed chimerism, particularly after human leukocyte antigen mismatched donor transplants, needs to be addressed.
EVALuna2:18905

Treosulfan-fludarabine-thiotepa-based conditioning treatment before allogeneic hematopoietic stem cell transplantation for pediatric patients with hematological malignancies - Kalwak, Krzysztof; Mielcarek, Monika; Patrick, Katharine; Styczynski, Jan; Bader, Peter; Corbacioglu, Selim; Burkhardt, Birgit; Sykora, Karl Walter; Drabko, Katarzyna; Gozdzik, Jolanta; Fagioli, Franca; Greil, Johann; et al. (Bone Marrow Transplantation, 2020)
Treosulfan-based conditioning prior to allogeneic transplantation has been shown to have myeloablative, immunosuppressive, and antineoplastic effects associated with reduced non-relapse mortality (NRM) in adults. Therefore, we prospectively evaluated the safety and efficacy of treosulfan-based conditioning in children with hematological malignancies in this phase II trial. Overall, 65 children with acute lymphoblastic leukemia (35.4%), acute myeloid leukemia (44.6%), myelodysplastic syndrome (15.4%), or juvenile myelomonocytic leukemia (4.6%) received treosulfan intravenously at a dose of 10 mg/m(2)/day (7.7%), 12 g/m(2)/day (35.4%), or 14 g/m(2)/day (56.9%) according to their individual body surface area in combination with fludarabine and thiotepa. The incidence of complete donor chimerism at day +28 was 98.4% with no primary and only one secondary graft failure. At 36 months, NRM was only 3.1%, while relapse incidence was 21.7%, and overall survival was 83.0%. The cumulative incidence of acute graft-vs.-host disease was 45.3% for grades I-IV and 26.6% for grades II-IV. At 36 months, 25.8% overall and 19.4% moderate/severe chronic graft-vs.-host disease were reported. These data confirm the safe and effective use of treosulfan-based conditioning in pediatric patients with hematological malignancies. Therefore, treosulfan/fludarabine/thiotepa can be recommended for myeloablative conditioning in children with hematological malignancies.
CRIS-Team WoS Importer:2020-04-07